2(7-3) fractional factorial optimization of polybenzimidazole based membrane electrode assemblies for H-2/O-2 fuel cells - Kannan, Ramaiyan; Islam, Md. Nazrul; Rathod, D.; Vijay, M.; Kharul, Ulhas K.; Ghosh, P. C.; Vijayamohanan, K. (Journal of Applied Electrochemistry, 2008)
We describe the usefulness of a statistical fractional factorial design to obtain consistent and reproducible behavior of a membrane-electrode-assembly (MEA) based on a phosphoric acid (PA) doped polybenzimidazole (PBI) membrane, which allows a H-2/O-2 fuel cell to operate above 150 degrees C. Different parameters involved during the MEA fabrication including the catalyst loading, amount of binder, processing conditions like temperature and compaction load and also the amount of carbon in the gas diffusion layers (GDL) have been systematically varied according to a 2(7-3) fractional factorial design and the data thus obtained have been analyzed using Yates's algorithm. The mean effects estimated in this way suggest the crucial role played by carbon loading in the gas diffusion layer, hot compaction temperature and the binder to catalyst ratio in the catalyst layer for enabling continuous performance. These statistically designed electrodes provide a maximum current density and power density of 1,800 mA cm(-2) and 280 mW cm(-2), respectively, at 160 degrees C using hydrogen and oxygen under ambient pressure.
Keywords: Carbon loading; Fractional factorial optimization; MEA; PBI; PEMFC

Design of an "allsolid-state'' supercapacitor based on phosphoric acid doped polybenzimidazole (PBI) electrolyte - Rathod, Dhanraj; Vijay, Meenu; Islam, Md. Nazrul; Kannan, Ramaiyan; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan (Journal of Applied Electrochemistry, 2009)
The effectiveness of phosphoric acid doped polybenzimidazole as a polymer electrolyte membrane to fabricate an all solid-state super capacitor has been explored using hydrous RuO(2)/carbon composite electrodes (20 wt.%) of surface area 250 m(2) g(-1) with many intrinsic advantages. The electrochemical evaluation of these super capacitors through cyclic voltammetry, charge/discharge and impedance measurements demonstrate the utility of this type of thin, compact and flexible supercapacitor capable of functioning at 150 degrees C to yield a maximum capacitance of about 290 F g(-1) along with a life of more than 1,000 cycles. A power density of 300 W kg(-1) and energy density of 10 Wh kg(-1) have been accomplished although the equivalent series resistance (ESR) of about 3.7 Omega needs to be reduced further for high rated applications.
Keywords: Electrochemical characterization; Electrochemical supercapacitor; Energy storage device; PBI electrolyte; RuO(2)/carbon composite

Variation in acid moiety of polybenzimidazoles: investigation of physico-chemical properties towards their applicability as proton exchange and gas separation membrane materials - Kumbharkar, S. C.; Islam, Md. Nazrul; Potrekar, R. A.; Kharul, Ulhas K. (Polymer, 2009)
A series of polybenzimidazoles (PBIs) were prepared from 3,3'-diaminobenzidine (DAB) and substituted aromatic dicarboxylic acids. Effects of added polarity, bulk and isomerism in the dicarboxylic acid moiety on the properties of formed aromatic polybenzimidazoles were investigated. Solution polycondensation procedure was optimized for individual case of PBI synthesis in order to obtain inherent viscosity of >= 1 dL/g. Analysis of physical properties, water uptake, acid doping (H(3)PO(4) and H(2)SO(4)) and gas permeability was performed. All these PBIs exhibited high thermal stability, good solvent solubility and amorphous nature. The uptake of H(3)PO(4) varied from 9 to 20.1 moles per repeat unit (mol/RU), H(2)SO(4) uptake varied from 3.39 to 3.81 mol/RU, while water uptake varied from 1.8 to 3.6 mol/RU of PBI. The dibromoterephthalic acid and tert-butylisophthalic acid based PBI showed the highest H(3)PO(4) uptake in the series, while tert-butylisophthalic acid based PBI exhibited the highest water uptake. Acid uptake was correlated with swelling of the PBI matrix, while density estimation of H(3)PO(4)-doped PBI by He gas expansion method could be correlated to the physical state of PBI. 5-tert-Butylisophthalic acid and 4,4'-(hexafluoroisopropylidene)bis(benzoic acid) based PBI exhibited higher H(2) and O(2) permeability than other PBIs. The ideal gas selectivity for O(2)/H(2) was considerably higher for most of the PBIs than conventional gas separation membrane materials. These analyses suggested that some of these PBIs have a potential to be used as a PEM or gas separation membrane material. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gas permeability; Polybenzimidazole; Proton exchange membrane